Edukasi Sosial Media Literasi pada Siswa Kelas VI SD Muhammadiyah Tonggalan, Klaten - Nisrina Akbar Rizky Putri; Noor Afy Shovmayanti; Ardiansyah Ardiansyah (WASATHON Jurnal Pengabdian Masyarakat, 2025)
The community service activity titled "Social Media Literacy Education for Sixth Grade Students at SD Muhammadiyah Tonggalan, Klaten" was designed to enhance the students' understanding and skills in utilizing information technology. Through education and direct guidance, this activity successfully improved students' knowledge in using social media, including crucial aspects such as data security and the accuracy of disseminated information. Additionally, the activity increased student’s awareness of the importance of privacy and security in technology usage. Although the results were positive, the report identifies several areas needing improvement, such as some students still sharing personal information, highlighting the need for broader collaboration with parties related to data security and information management skills, expanding participant reach, and developing more comprehensive educational materials